ANALISIS PENERAPAN FUNGSI PERENCANAAN DAN PENGAWASAN DALAM MENINGKATKAN EFEKTIVITAS KERJA KARYAWAN KOPERASI (STUDI KASUS PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk) - Sari Sakarina (Jurnal Ilmiah Ekonomi Global Masa Kini)
Cooperative employees of PT. Bank Rakyat Indonesia (Persero) Tbk, is a cooperative engaged in savings and cooperative stores which have a work area in an office environment BRI. At the cooperative of employees of BRI is the duty and obligation of the Agency inspectors have not been implemented properly, where inspection is only carried out ahead of the Annual Members Meeting (RAT) only, whereas the investigation carried out by the Inspection Cooperative employees of Bank BRI merely move the data that has been processed or prepared by the board and not the result and the actual examination or observation.Inspection is only carried out at the cooperative office only, and not descend directly on the existing business units, so that the problems that exist in the unit and the solution is not known with certainty. Results of the examination and the content of the report submitted to the Annual Members Meeting (RAT) is generally stated that the implementation of activities and cooperative efforts go well, and also never held sudden inspection.As for the problem of this research is "How can the application of planning and oversight function in increasing the effectiveness of employees cooperative PT.Bank Rakyat Indonesia (Persero) Tbk". In order for the company's activities can be run effectively and precisely target the company would need to know the consumer perception that creates a purchase decision, in particular by:1. To overcome the limited executive power then it takes an expert in the field of business units and the need for education and training programs to improve work effectiveness.2. To overcome these limitations problem then each subordinate need a lot of expertise in their respective fields.3. In order for the planning process can be run according to plan, the first set in advance the type of business that this factor is the main basis in setting the plan.